KEBIJAKAN DAN STRATEGI PEMBANGUNAN PERKOTAAN NASIONAL DI INDONESIA - Angga Sulaiman (Jurnal Ilmu dan Budaya, 2018)
The rapid phenomenon of city growth is not only happening in Indonesia, it is also experienced in various countries in the world, where urbanization is suspected to be a major factor of rapid growth. In the context of Indonesia, the urban conditions of today are confronted by the complexity of the problems within which indicate urban environmental degradation. So thispaper will describe the direction of policies and strategies of urban development in Indonesia that aims to provide an overview of national urban development efforts. Using descriptive methods, information is obtained from a variety of relevant documents that will explicitly describe City Vision and Mission 2050, regulatory framework, strategic issues, policy directions,targets and urban development strategies based on the National Medium Term Development Plan 2015 - 2019.